2-D model of the streamer zone of a leader. (13th January 2016) - Milikh, G. M.; Likhanskii, A. V.; Shneider, M. N.; Raina, A.; George, A.
Abstract : Formation of the streamer zone of a leader is an outstanding problem in the physics of electric discharges which is relevant to laboratory leaders, as well as to the leaders formed by lightning. Despite substantial progress in the theoretical understanding of this complicated phenomenon, significant puzzles, such as the low propagation velocity of a leader compared to the fast streamers, remain. The objective of this paper is to present 2-D plasma simulations of the formation and propagation of the streamer zone of a leader. In these simulations we will generate a group of streamers that propagate in a discharge gap while interacting with each other. It is shown that interaction between the streamers significantly reduces their propagation velocity. This explains why the leader, which consists of many streamers, is much slower than a single streamer formed in the same discharge gap. It is shown that the mean velocity suppression of the group of streamers is determined by the inter-streamer distance. The critical value of the packing factor of the streamers at which the interactions between them can be neglected, and thus the discussed process can be treated as caused by a single streamer, is obtained.